ARTIFICIAL INTELLIGENCE IN EMOTIONAL INTELLIGENCE: A TRANSFORMATIVE ROLE OF CHATGPT IN MEDICAL EDUCATION - RASHID, SULTHAN AL; SURIYAN, ARUN; B, RAVITHRAA (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
The complexities of modern healthcare demand more than technical expertise. Emotional intelligence (EI) has emerged as an essential skill for medical professionals, allowing them to deliver compassionate care, foster teamwork, and maintain their well-being in a high-stress environment. EI, popularized by Daniel Goleman, is defined as the ability to perceive, understand, and regulate emotions effectively in oneself and others. For medical students, developing EI is as critical as mastering clinical skills, as it directly influences patient outcomes, decision-making, and professional resilience [1-5]. Despite its importance, incorporating EI into medical education remains a challenge. Traditional methods such as workshops, reflective exercises, and simulations are effective but limited by resource constraints and subjective assessments. This creates an opportunity to explore innovative tools, like ChatGPT, to enhance EI training. ChatGPT, a conversational AI developed by OpenAI, can simulate real-world scenarios, facilitate guided reflection, and provide iterative feedback, making it a valuable adjunct to traditional methods.